Analisis Yuridis Kebijakan Hukuman Mati di Indonesia - Zulhilmi, Daffa; Chaidar, Muhamad (Universitas Muhammadiyah Ponorogo, 2025)
The death penalty is the highest form of punishment still applied in Indonesia, especially for serious crimes such as premeditated murder, narcotics, and terrorism. This policy has a clear legal basis in the Criminal Code and a number of special laws. However, its implementation has raised debates regarding its impact on human rights, especially the right to life guaranteed by the constitution. This study aims to examine the legal basis, history and evolution of the death penalty policy, its impact on human rights, and its implementation in the context of law enforcement in Indonesia. This study uses a normative legal method with a legislative, conceptual, and historical approach, as well as qualitative data analysis of primary and secondary legal materials to understand the legal basis, objectives, and implications of the implementation of the death penalty in Indonesia. The results of the study show that although the death penalty has strong legal legitimacy, its implementation faces serious challenges, such as criticism of its effectiveness in preventing crime and potential violations of procedural justice, especially for less fortunate defendants. International pressure has also encouraged Indonesia to consider progressive steps, such as implementing a moratorium or abolishing the death penalty. This study concludes that the death penalty needs to be thoroughly evaluated to be more in line with human rights principles. A moratorium could be the first step in reforming more humane and effective sentencing policies.